Factors affecting presence of feed in crops of broilers at slaughter : with focus on a hygienic slaughter - Eriksson, Ylva (SLU/Dept. of Animal Nutrition and Management (until 231231), 2022)
Food security and sustainable consumption and production are parts of the United Nation Sustainable Development Goals 2 and 12. Filled broiler crops at slaughter poses a risk to contaminate carcasses with gastrointestinal contents. Due to the risk of contamination of pathogenic and other bacteria, the carcasses will be rejected for further processing if contaminated. The purpose of this thesis was to investigate which factors that influence the content load of crops at slaughter, and possibilities to reduce the problem. Furthermore, investigation if rinsing can improve the hygienic quality of carcasses. This was done by palpation of the crop in live birds at farms, interviewing of producers, observations of the assessment of filled crops at slaughter, and by analyses of the load of total aerobic bacteria and Enterobacteriaceae before and after rinsing of carcasses at slaughter. The result of the interviews with farmers revealed that on-farm factors had no significant effect on the percentage of filled crops at slaughter. However, a significant difference in the percentage of crops assessed as filled was observed for the two working shifts in the meat inspection. Rinsing of carcasses resulted in a significantly decrease in total aerobic bacteria and Enterobacteriaceae, which is a positive result towards improving the hygienic quality of the carcasses. In conclusion, results from this thesis show that further research within this topic is required to better understand which factors that are linked to broiler crops assessed as filled at the slaughterhouse and to ensure a hygienic slaughter. A better understanding of which factors affecting the occurrence in filled crops at slaughter will be of importance for the continuous work toward the Sustainable Development Goals 2 and 12.